2010
DOI: 10.1002/cncr.25560
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of amphiregulin expression in patients with epidermal growth factor receptor (EGFR) wild‐type nonsmall cell lung cancer treated with EGFR‐tyrosine kinase inhibitors

Abstract: The current results suggested that patients with WT EGFR-positive NSCLC who have AR-positive tumors may benefit clinically from treatment with EGFR TKIs, indicating that AR expression may be a potential marker for the selection of EGFR-TKI treatment for patients with WT EGFR-positive NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 44 publications
2
36
2
1
Order By: Relevance
“…Our study showed for the first time that high AREG expression in SCCHN tumors is an independent prognosticator of poor outcome on cetuximab-docetaxel treatment. This is in clear contrast to the results from clinical studies of mCRC (14,15) and NSCLC (26), in which the clinical activity of treatment with the EGFR targeting agents cetuximab, gefitinib, or erlotinib was positively associated with AREG expression. Technical differences in the AREG immunostaining methods as a possible reason for differences in the prognostic value of AREG expression levels are rather unlikely because the same antibody was used in the NSCLC (26) and our study.…”
Section: Discussioncontrasting
confidence: 98%
“…Our study showed for the first time that high AREG expression in SCCHN tumors is an independent prognosticator of poor outcome on cetuximab-docetaxel treatment. This is in clear contrast to the results from clinical studies of mCRC (14,15) and NSCLC (26), in which the clinical activity of treatment with the EGFR targeting agents cetuximab, gefitinib, or erlotinib was positively associated with AREG expression. Technical differences in the AREG immunostaining methods as a possible reason for differences in the prognostic value of AREG expression levels are rather unlikely because the same antibody was used in the NSCLC (26) and our study.…”
Section: Discussioncontrasting
confidence: 98%
“…Interestingly, it was recently reported that high amphiregulin expression could be coupled to shortened overall and progression-free survival during treatment for HNSCC with a combination of cetuximab and docetaxel (Tinhofer et al 2011), thus being a negative predictor of cetuximab response. It was suggested that tissue-specific functions of amphiregulin might explain the contradictory findings in mCRC (Jacobs et al 2009;Khambata-Ford et al 2007), NSCLC (Chang et al 2011;Yonesaka et al 2008) and HNSCC. An observation from our work is that several of the cell lines that release amphiregulin under ordinary growth conditions do not release more growth factor when treated with ligand-binding competitor.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Chang et al [28] analyzed the expression of amphiregulin, a novel molecular biomarker, in patients with EGFR wild-type NSCLC who were treated with EGFR-TKIs. They reported that, although the relationship with DCR was not statistically significant, positive amphiregulin status using immunohistochemical staining was associated with prolonged PFS and OS.…”
Section: Discussionmentioning
confidence: 99%